2013
DOI: 10.1124/dmd.113.051680
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assessment of the Impact of Efflux Transporter on Oral Drug Absorption Using Portal Vein–Cannulated Rats

Abstract: The purpose of this study was to evaluate the impact of intestinal efflux transporters on the in vivo oral absorption process. Three model drugs-fexofenadine (FEX), sulfasalazine (SASP), and topotecan (TPT)-were selected as P-glycoprotein (P-gp), breast cancer resistance protein (BCRP), and P-gp and BCRP substrates, respectively. The drugs were orally administered to portal veincannulated rats after pretreatment with zosuquidar (ZSQ), P-gp inhibitor, and/or Ko143, BCRP inhibitor. Intestinal availability (Fa·Fg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…100.65 ± 33.07 ng/mL, P < 0.05) and 48% (1,457.59 ± 487.86 h·ng/mL vs . 982.29 ± 357.09 h·ng/mL, P > 0.05) increase in rats with the pretreatment of zosuquidar, a specific P‐gp transporter with the oral dosage of 30 mg/kg . Additionally, the prolonged T max (2.17 ± 0.98 h vs .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…100.65 ± 33.07 ng/mL, P < 0.05) and 48% (1,457.59 ± 487.86 h·ng/mL vs . 982.29 ± 357.09 h·ng/mL, P > 0.05) increase in rats with the pretreatment of zosuquidar, a specific P‐gp transporter with the oral dosage of 30 mg/kg . Additionally, the prolonged T max (2.17 ± 0.98 h vs .…”
Section: Resultsmentioning
confidence: 95%
“…Consistent to the in vitro experiment (as seen in Part 1) that the generation of NTR could happen in the MGF‐incubating enterobacteria samples, but not in hepatocytes, and it only accounted for 0.1% of the adding MGF concentration after incubation within 72 h, as well as where the MGF concentration remained very limited changes, implying that NTR production mainly mediated by intestinal bacteria, but it accounted for a tiny percentage of the parent drug in the intestinal lumen and thereby it was not sufficiently enough to change the PK profiles of MGF in vivo . Compared with MGF treatment alone, the C max and AUC of MGF displayed 210% and 48% enhancement in rats with the pretreatment of zosuquidar, a specific P‐gp inhibitor that significantly increased the exposure of fexofenadine in rats by the inhibition of P‐gp transporters at the oral dosage of 30 mg/kg . Correspondingly, verapamil, a typical P‐gp inhibitor, could enhance the transport on MGF transport in Caco‐2 cell monolayer model .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…9 Matsson et al (2005) reported that the rank-order correlation between the Fa of P-gp substrates and their P app values determined in the Caco-2 cell monolayer was better than that in the 2/4/A1 cell monolayer. Furthermore, the Fa value of sulfasalazine, the intestinal absorption of which was limited by BCRP and MRP2 in Caco-2 cells, 30 in rats, 31,32 and in clinical studies, [33][34][35] was overpredicted in 2/4/A1 cells by the best-fitted regression line for the relationship between the P app value in 2/4/A1 cells and observed Fa value. 6 However, the Fa value for the same drug was predicted well by P app values in HIECs (observed Fa ¼ 13% vs. predicted Fa ¼ 15% obtained from the best-fitted sigmoidal relationship in Fig.…”
Section: Discussionmentioning
confidence: 90%
“…These results demonstrate that BCRP significantly contributes to the transport of these drugs in Caco-2 cell monolayers. Matsuda et al (2013) demonstrated that the intestinal availability of topotecan and sulfasalazine after oral administration in rats was increased by approximately 4-fold following the preadministration of Ko143. Moreover, Dahan et al (2009) showed that the BCRP inhibitors fumitremorgin C and pantoprazole significantly increased the AP-to-BL transport of sulfasalazine.…”
Section: Discussionmentioning
confidence: 99%